Oral Hygiene Status and Dental Caries Experience Among Young Adults Reporting to A Private Dental Institution in Chennai - A Retrospective Analysis - P.S, KARTHIKESON.; SAKTHI, SRI; KUMAR P, KIRAN (The journal of contemporary issues in business and government, 2021)
Dental caries is a widespread chronic disease affecting billions of people worldwide. Dental caries can be an unfavourable sequelae of improper oral hygiene. Dental caries is regarded as mostly the disease of young age. Analysing a trend of dental caries experience and oral hygiene in young people would help in formulating and providing a comprehensive approach in treating this population. This retrospective cross sectional study is done among young adult patients of private dental hospital. Oral hygiene status and dental caries data was collected from patient records between June 2019 to March 2020. Collected data was entered in excel and exported to SPSS version 22 for software analysis. A chi square analysis was done and a p value < 0.05 was considered to be statistically significant. Total records included in the study were 303, belonging to the young adults category.Overall OHIS score among young adults was found to be fair (27%) in the 18-20 years age group,49% fair in the 23-25 years age group. Overall dental caries experience [DMFS,DMFT scores] was found to be 25% fair in the 18-20 years age group ,25% good in the 21-22 years age group, 50% fair in the 23-25 years age group.Within the limitations of current study, overall oral hygiene status was found to be fair and moderate risk of dental caries experience among young adults was seen.